The English Translation of Goenawan Mohamad’s On God and Other Unfinished Things with Special Reference to Poem No. 15: Reiss’ Method Application - Almira Ghassani Shabrina Romala; Harris Hermansyah Setiajid (Universitas Dian Nuswantoro, 2018)
This paper aims to explicate and examine one of the poems written by Goenawan Mohamad, Poem No. 15, which is included in his poem and poetic essay collection entitled Tuhan dan Hal-hal yang Tak Pernah Selesai, which was translated into On God and Other Unfinished Things by Laksmi Pamuntjak by applying Reiss’ method. This method scrutinizes the translation shift, especially the expression shift and the intralinguistic criteria comprising semantic, lexical, grammatical, and stylistic features. As a creative composition and a piece of literary work that illuminates the imaginative, emotional, and intellectual experience and creativity of its author, a poem is classified in the expressive text type based on Reiss’ text-type category. The result shows that there are several intralinguistic criteria and stylistic features maintained and also modified by the translator in the English translation of Goenawan Mohamad’s Poem No. 15 in On God and Other Unfinished Things, that is done not only to preserve the aesthetic dimension of the language used in the poem but also to fulfill the expressive function of the text. By employing various translation shifts and metaphor translation to make the target text more natural, preserving the relevant aspects of the semantic content, and taking the standpoint of the author in translating the poem, the English translation of Poem No. 15 can fulfill its quality assessment required by its expressive text type.